THE BASIC APPROACHES TO THE PROBLEM OF UNDERSTANDING AND THE EXPLANATION IN HISTORY OF THE PHILOSOPHICAL IDEA - Ulyana Vladimirovna Bolotova (Современная наука и инновации, 2022)
Article is devoted to consideration of a problem of the understanding, being by one of the eternal philosophical problems, aggravated as the importance of the given term for the philosophical theory, and its polysemy. The specific context understandings has been created in the end of the last century when understanding began to be opposed with an explanation or, at least, the given terms have ceased to be considered as synonymous.